Degradation of Typical Indoor Air Pollutants Using Fe-Doped TiO2 Thin Film under Daylight Illumination. (2nd March 2014) - Wang, Shuaijie; Yu, Hao; Cheng, Xingxing
Abstract : A type of iron-doped titania thin film was prepared by means of sol-gel method to degrade indoor formaldehyde (HCHO), ammonia (NH3 ), and benzene (C6 H6 ) under sunlight. The photocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-Vis spectroscopy, and energy dispersive spetra (EDS). The results showed that the iron was doped in the TiO2 photocatalyst successfully. The absorption edge of doped TiO2 had red shifts and the doped TiO2 had a stronger absorption than the pure TiO2 in the visible region. Fe-doped TiO2 thin film prepared with the optimal preparation condition could remove indoor HCHO, NH3 and C6 H6 effectively under solar light irradiation. The removal percentage of HCHO, NH3 or C6 H6 after 9 h photocatalytic reaction under solar light reached 55%, 53.1%, and 37.5%, respectively, when they existed in the air individually. When the three pollutants were mixed in the air, the removal percentage decreased to 33.3%, 28.3%, and 28%. The degradation reaction of the three pollutants followed the pseudo first-order kinetics, which reflects that the photocatalytic reaction was controlled by the surface chemical reaction and the reaction rate was controlled by concentration of reactants.